Voltage‐Modulated Untwist Deformations and Multispectral Optical Effects from Ion Intercalation into Chiral Ceramic Nanoparticles. Issue 16 (16th March 2023) - Shao, Xiao; Zhu, Cheng; Kumar, Prashant; Wang, Yanan; Lu, Jun; Cha, Minjeong; Yao, Lin; Cao, Yuan; Mao, Xiaoming; Heinz, Hendrik; Kotov, Nicholas A.
Abstract: Reconfiguration of chiral ceramic nanostructures after ion intercalation should favor specific nanoscale twists leading to strong chiroptical effects. In this work, V2 O3 nanoparticles are shown to have "built‐in" chiral distortions caused by binding of tartaric acid enantiomers to the nanoparticle surface. As evidenced by spectroscopy/microscopy techniques and calculations of nanoscale chirality measures, the intercalation of Zn 2+ ions into the V2 O3 lattice results in particle expansion, untwist deformations, and chirality reduction. Coherent deformations in the particle ensemble manifest as changes in sign and positions of circular polarization bands at ultraviolet, visible, mid‐infrared (IR), near‐IR (NIR), and IR wavelengths. The g‐ factors observed for IR and NIR spectral diapasons are ≈100–400 times higher than those for previously reported dielectric, semiconductor, and plasmonic nanoparticles. Nanocomposite films layer‐by‐layer assembled (LBL) from V2 O3 nanoparticles reveal cyclic‐voltage‐driven modulation of optical activity. Device prototypes for IR and NIR range problematic for liquid crystals and other organic materials are demonstrated. High optical activity, synthetic simplicity, sustainable processability, and environmental robustness of the chiral LBL nanocomposites provide a versatile platform for photonic devices. Similar reconfigurations of particle shapes are expected for multiple chiral ceramic nanostructures, leading to unique optical, electrical, and magnetic properties. Abstract : Chiral V2 O3 nanoparticles display rich palette of intense chiroptical bands. Intercalation–deintercalation of Zn 2+ leads to twist–untwist deformation and modulation of optical activity, which is remarkably strong for IR and NIR range because V2 O3 nanoparticles have g ‐factors ≈100–400 times higher than other nanostructures. Device prototypes based on layer‐by‐layer assembled nanocomposite films provide a pathway to versatile voltage‐driven photonic devices.